Overexpression of alfalfa SIMK promotes root hair growth, nodule clustering and shoot biomass production - Hrbáčková, Miroslava; Luptovčiak, Ivan; Hlaváčková, Kateřina; Dvořák, Petr; Tichá, Michaela; Šamajová, Olga; Novák, Dominik; Bednarz, Hanna; Niehaus, Karsten; Ovečka, Miroslav; Šamaj, Jozef (Plant biotechnology journal, 2021)
Nitrogen-fixing rhizobia and legumes have developed complex mutualistic mechanism that allows to convert atmospheric nitrogen into ammonia. Signalling by mitogen-activated protein kinases (MAPKs) seems to be involved in this symbiotic interaction. Previously, we reported that stress-induced MAPK (SIMK) shows predominantly nuclear localization in alfalfa root epidermal cells. Nevertheless, SIMK is activated and relocalized to the tips of growing root hairs during their development. SIMK kinase (SIMKK) is a well-known upstream activator of SIMK. Here, we characterized production parameters of transgenic alfalfa plants with genetically manipulated SIMK after infection with Sinorhizobium meliloti. SIMKK RNAi lines, causing strong downregulation of both SIMKK and SIMK, showed reduced root hair growth and lower capacity to form infection threads and nodules. In contrast, constitutive overexpression of GFP-tagged SIMK promoted root hair growth as well as infection thread and nodule clustering. Moreover, SIMKK and SIMK downregulation led to decrease, while overexpression of GFP-tagged SIMK led to increase of biomass in above-ground part of plants. These data suggest that genetic manipulations causing downregulation or overexpression of SIMK affect root hair, nodule and shoot formation patterns in alfalfa, and point to the new biotechnological potential of this MAPK.
Keywords: rostlinné proteiny; SIMKK; Symbiosis; SIMK; mitogenem aktivované proteinkinasy kinas; Medicago sativa; Biomass; root hair; symbióza; Mitogen-Activated Protein Kinase Kinases; Plant Proteins; infection thread; Cluster Analysis; shluková analýza; biomasa; nodule